Investigating the psycho-educational challenges of HIV and AIDS orphans in Mphaki, Quthing - Ranthamane, Rosina Makhethang (University of the Free State, 2020)
The human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) have been the leading cause of orphanhood in sub-Saharan Africa, including Lesotho (Ramjatan, 2015). Many parents die at the productive stage and their children are left with elders or in child-headed families, leaving these orphaned children with many challenges. The study focused on investigating the psycho-educational challenges of HIV and AIDS orphans. The theoretical framework that guided the study was Maslow’s hierarchy of needs supported by Bronfenbrenner’s ecological systems theory. The study used a qualitative research design. This incorporated drawing as visual-participatory method and unstructured interviews as methods for collecting data. Nine HIV- and AIDS-orphaned learners and three of their teachers from rural primary schools participated in the research, making a total of 12 participants. The prompt, “What challenges do you experience as orphans in day-to-day life activities?” was used as a tool to guide learner participants in drawing the challenges they experience in everyday life. The teachers were interviewed to triangulate and supplement the information obtained from the learners. Results revealed that orphans experience economic, social and psychological challenges that affect their learning and their education as a whole. Some challenges include basic needs such as food, clothes, shelter, love, and educational needs. Common educational challenges include absenteeism, poor performance, punctuality problems and lack of concentration. The findings further revealed that orphans do receive support from the government, non-governmental organisations (NGOs) and other stakeholders, but these are not enough to contribute to the holistic development of orphans.
Dissertation (M.Ed. (Psychology of Education))--University of the Free State, 2020
Keywords: HIV and AIDS; Needs; Orphans; Psycho-educational challenges